Socioeconomic status and benzodiazepine and Z-drug prescribing: a cross-sectional study of practice-level data in England. (22nd October 2019) - Soyombo, Stephanie; Stanbrook, Rhian; Aujla, Harpal; Capewell, David; Shantikumar, Mary; Kidy, Farah; Todkill, Daniel; Shantikumar, Saran
Abstract: Background: Benzodiazepines and Z-drugs (such as zopiclone) are widely prescribed in primary care. Given their association with addiction and dependence, understanding where and for whom these medications are being prescribed is a necessary step in addressing potentially harmful prescribing. Objective: To determine whether there is an association between primary care practice benzodiazepine and Z-drug prescribing and practice population socioeconomic status in England. Methods: This was a cross-sectional study. An aggregated data set was created to include primary care prescribing data for 2017, practice age and sex profiles and practice Index of Multiple Deprivation (IMD) scores—a marker of socioeconomic status. Drug doses were converted to their milligram-equivalent of diazepam to allow comparison. Multiple linear regression was used to examine the association between IMD and prescribing (for all benzodiazepines and Z-drugs in total, and individually), adjusting for practice sex (% male) and older age (>65 years) distribution (%). Results: Benzodiazepine and Z-drug prescribing overall was positively associated with practice-level IMD score, with more prescribing in practices with more underserved patients, after adjusting for age and sex ( P < 0.001), although the strength of the association varied by individual drug. Overall, however, IMD score, age and sex only explained a small proportion of the overall variation in prescribing across GP practices. Conclusion: Our findings may, in part, be a reflection of an underlying association between the indications for benzodiazepine and Z-drug prescribing and socioeconomic status. Further work is required to more accurately define the major contributors of prescribing variation.